Evaluation of the Relationship Between Biomarkers and Disease Severity in Patients with Community-Acquired Pneumonia - Yeşildağ, Mihrican; Özkan Bakdık , Bengü; Balasar, Barış; Eroğlu, Esma (European Journal of Therapeutics, 2024)
Objective: Biomarkers in community-acquired pneumonia (CAP) have the potential to facilitate clinical decisions by guiding the prediction of disease severity, treatment and prognosis. In this study, we evaluated the relationship of biomarkers with disease severity in patients with CAP. Methods: 156 patients diagnosed with CAP were included in the study. Diagnosis of CAP was determined according to the Infectious Diseases Society of America (IDSA)/ American Thoracic Society(ATS) 2019 guidelines along with clinical findings. The CRB-65 scoring system was used to determine outpatient and hospitalized patients. Patient information was obtained retrospectively from their files. In these two patient groups; C-reactive protein (CRP), complete blood count (CBC) parameters, neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), monocyte/neutrophil ratio (MNR), lymphocyte/monocyte ratio (LMN), lymphocyte/CRP ratio (LCR), WBC/mean platelet volume ratio (WBC/MPV), CRP/MPV ratio, and MPV/PLT ratio were examined. Results: Of the 156 patients included in the study, 72 were pneumonia patients receiving inpatient treatment (mean age 66.88±16.29) and 84 patients receiving outpatient treatment (mean age 51.57±16.68). Age was found to be statistically significant between the groups (p< 0.001). In the inpatient group; CRP, WBC, neutrophil, lymphocyte, monocyte, basophil, hemoglobin, hematocrit, MPV, NLR, PLR, LMR, NMR, LMR, LCR, WBC/MPV, and CRP/MPV were found to be significantly high (p<0.05). Parameters with diagnostic performance that may be helpful in distinguishing hospitalized patients with pneumonia are CRP/MPV (AUC:0.775, 95% CI:0.701-0.850), NLR (AUC:0.771, 95% CI:0.697-0.846) and CRP (AUC:0.758, 95% Cl:0.679-0.837). Conclusion: NLR and CRP/MPV values, which can be measured easily and quickly together with CRP, can be used as additional tests to help distinguish patients with pneumonia requiring hospitalization.